An Examination of the Scope and Stereochemistry of the Ireland–Claisen Rearrangement of Boron Ketene Acetals. Issue 15 (3rd March 2014) - Seizert, Curtis A.; Ferreira, Eric M.
Abstract The Ireland–Claisen rearrangement of boron ketene acetals is described. The boron ketene acetal intermediates are formed through a soft enolization that obviates the use of strong bases and the intermediacy of alkali metal enolates. Yields and diastereoselectivities of these rearrangements are very sensitive to the choice of boron reagent, even among those that have been shown to effect quantitative formation of boron ketene acetals from esters. The rearrangement occurs at room temperature for all substrates with generally high levels of stereoselectivity. In contrast to previous reports using boron triflates, the use of a commercially available boron iodide reagent allows for a wider substrate scope that extends to propionates and arylacetates, as well as the previously described α‐oxygenated esters. This work also provides insight into the dynamic nature of boron ketene acetals and the ramifications of this behavior for reactions in which they are intermediates.